HE ROLE OF FATTY ACID CONTENTS OF ERYTHROCYTES MEMBRANES IN CARDIOHEMODYNAMICS DISORDER IN GOUT PATIENTS WITH INSULIN RESISTANCE SYNDROME - N. N. Kushnarenko; T. A. Medvedeva; A. V. Govorin; M. Yu. Mishko (Российский кардиологический журнал)
Aim. To assess the specifics of fatty acidic contents of erythrocyte membranes, and morpho-functional disorder of the left ventricle (LV) in gout patients depending on the syndrome of insulin resistance (IR).Material and methods. In the study, 117 males participated, age 39 to 55 y o., with gout. Among them, 43.6% presented with normal HOMA-IR, and the rest had IR. Fatty acid content of membrane lipids assessed, as the morphofunctional properties of theLV, with the types ofLV geometry and its diastolic function assessment, according to presence or absence of IR.Results. Changes of fatty acid contents in IR and gout patients cells membranes are characterized by increased amount of saturated fatty acids and decreased — of unsaturated, and in the pool of unsaturated acids there is increase of monoenic, but significant decrease of polyenic acids. In the pool of polyunsaturted acids there is increased amount of y-linoleic and dihomo-y-linoleic and significant decrease of arachidonic and docosapentaenoic acids. It is found, that cardiohemodynamics parameters in gout patients do significantly differ with IR. In males with gout and IR the prevailing variant of theLV architectonics was concentric hypertrophy (49,3%; p<0,05). Patients with the normal parameters of glucose-insulin homeostasis more commonly showed normal geometry (26,6%; p<0,05) and eccentric hypetrophy ofLV (46,8%; p<0,05). Diastolic dysfunction of theLV was registered 2,8 times more frequently in the insulin resistant patients. There were correlations found of hyperuricaemia, increased insulin level and changes of fatty acidic content and cardiohemodynamics parameters.Conclusion. The found relations of the fractional contents of fatty acids, morphofunctional disorder of theLV and parameters of carbohydrate metabolism might impact significantly the development of cardiovascular complications in this category of patients.